2021
DOI: 10.1186/s12903-021-01766-y
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement and associated factors among dental nurses in China

Abstract: Background Work engagement is affected by many factors. The level of work engagement among dental nurses is unknown. Methods A cross-sectional questionnaire survey was conducted among 215 dental nurses. The Utrecht Work Engagement Scale, Chinese Nurse Stressors Scale, Work-related Acceptance and Action Questionnaire, Multi-dimensional Scale of Perceived Social Support, and General Well-Being Schedule were applied to measure Chinese nurses’ work eng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 53 publications
3
29
1
Order By: Relevance
“…Secondly, this study found that the job engagement of surgical nurses was signi cantly different from that of nurses in pediatrics and other departments, which was different from Wang's study [41] that there was no difference between departments. This may be related to the short hospital stay of surgical patients, high admission and discharge rate, and relatively high salaries of nurses.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Secondly, this study found that the job engagement of surgical nurses was signi cantly different from that of nurses in pediatrics and other departments, which was different from Wang's study [41] that there was no difference between departments. This may be related to the short hospital stay of surgical patients, high admission and discharge rate, and relatively high salaries of nurses.…”
Section: Discussioncontrasting
confidence: 87%
“…Some literature showed that job engagement is closely related to nancial return, job performance, turnover intention, and employee creativity [43][44][45][46]. This result is different from Wang's [41].opinion that annual household income does not affect the job involvement of dental nurses. Also in Hu's [39] study of nurses in the emergency department, it was found that monthly salary did not affect their job engagement.…”
Section: Discussionmentioning
confidence: 90%
“…In our study, the average score of work engagement of ICU nurses was 33.85, and the scoring rate was only 62.7%, which was consistent with the results of other studies on work engagement of ICU nurses (Mason et al, 2014;van Mol et al, 2018), but significantly lower than that of general department nurses (Buckley et al, 2021;Manning, 2016;Wang et al, 2021) nurses. On the other hand, the results also support the clinical significance of paying attention to the nurses' work engagement and exploring the influencing factors.…”
Section: Outcome Of Work Engagementsupporting
confidence: 92%
“…The empirical studies show that the composite reliability (CR) and convergent validity (CV) were .87–.92 and .80–.89, respectively. The correlation between subscales is in the range of .78–.95 (Wang, Gao, et al, 2021; Zhu et al, 2015). The Cronbach's α coefficient of this sample was .94 and those of three subscales ranged from .92–.96.…”
Section: Methodsmentioning
confidence: 99%